Fabrication of levofloxacin-loaded ph-sensitive eudragit polymeric floating microballoon biomaterial for gastroretentive drug delivery - Prakash, Manivasakam; Nallasamy, Venkateswaramurthy; Venkatachalam, Senthil (Journal of Applied Pharmaceutical Research, 2025)
Background: The design of improved biomaterials for medication administration is vital in overcoming problems associated with standard therapy for Helicobacter pylori (H. pylori)-induced stomach ulcers. This study aims to develop and characterize floating biomaterial of levofloxacin microballoon biomaterials based on a fluoroquinolone-benzoxazine system conjugated with methylated piperazine and carboxylic acid groups, strategically designed for prolonged gastric delivery. Methodology: Using the emulsion solvent diffusion method, thirteen preparations were developed by different polymer ratios (pH-sensitive Eudragit RS-100 and Ethyl Cellulose), stirring speeds, and temperatures. Results and Discussion: In the buoyancy study simulated gastric fluid (pH 1.2), the best formulation (F9) shows superior encapsulation efficiency (90.2%) and sustained drug release profile (91.2% over 8 hours) that increases its effectiveness against H. pylori. FTIR and SEM analyses conducted during characterization studies verified the drug stability and the spherical microballoon morphology, with a particle size of 81.2 µm. Levofloxacin-loaded microballoon biomaterials provide a unique gastro-retentive delivery system that improves patient compliance, reduces off-target effects, and maintains effective drug concentrations at the infection site, thereby strengthening the therapeutic efficacy of levofloxacin against H. pylori. Conclusion: This creative method offers a viable substitute for traditional therapies for stomach ulcers and is consistent with the overarching objectives of targeted delivery systems and structure-based drug development.